2011
DOI: 10.1039/c1ce05094j
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of highly b-oriented zeolite MFI films by suppressing twin crystal growth during the secondary growth

Abstract: Highly b-oriented MFI films are synthesized by simply controlling TPA + concentration of the secondary synthesis solution to suppress the formation of a-oriented crystals. A formation mechanism is discussed for the films and also in the context of general MFI nucleation and crystallization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
49
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 32 publications
1
49
0
Order By: Relevance
“…[25] In this work, we therefore first tried the synthesis with ac omposition of 0.1 TPABr:SiO 2 :165 H 2 O (TPA + /Si = 0.1) for the secondary growth. [25] In this work, we therefore first tried the synthesis with ac omposition of 0.1 TPABr:SiO 2 :165 H 2 O (TPA + /Si = 0.1) for the secondary growth.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[25] In this work, we therefore first tried the synthesis with ac omposition of 0.1 TPABr:SiO 2 :165 H 2 O (TPA + /Si = 0.1) for the secondary growth. [25] In this work, we therefore first tried the synthesis with ac omposition of 0.1 TPABr:SiO 2 :165 H 2 O (TPA + /Si = 0.1) for the secondary growth.…”
mentioning
confidence: 99%
“…Figure 1p resents the SEM images of the b-oriented MFI zeolite seed layer on ag lass plate prepared by hand-rubbing ( Figure 1a)and the evolution of the zeolite film morphology along with the crystallization time (Figure 1b-d). [8,25] Due to the aggregation of undissolved fumed silica during hydrothermal synthesis,asemi-solid gel was formed after crystallization. Acontinuous and twinfree b-oriented zeolite film can be achieved when the time is prolonged to 24 h( Figure 1d).…”
mentioning
confidence: 99%
“…They also found that high-quality b -oriented MFI-type zeolite fi lms could be obtained by microwave synthesis on the base of the above pretreatment method [ 54 ]. Wang et al found that twin growth of a b -oriented MFI seed layer could be effectively suppressed by decreasing the TPA + / Si ratio in the secondary synthesis solution to a certain value (e.g., <0.01) [ 55 ].…”
Section: Oriented Mfi-type Zeolite Films and Membranesmentioning
confidence: 97%
“…The rub coating is a simple and effective way to coat zeolite seeds on the support surface, especially defective porous supports because zeolite seeds can fi ll the defect pores in the support by rub coating. A b -oriented MFItype seed layer can also be prepared by rub coating coffi n-shaped MFI-type zeolite seed crystals on dense supports (glass slides, silicon wafers, and metal plates) [ 55 ]. Wang et al developed a novel seeding method, dip coating-wiping seeding, for ceramic hollow fi ber supports [ 29 ].…”
Section: Seeded Growthmentioning
confidence: 99%
“…[15] To solve this problem, rapid thermal processing [11c] and molecular layer deposition [16] have been reported to fabricate defect-free molecular-sieve membranes.H owever, the complexity of those methods limits their widespread application in industry.…”
mentioning
confidence: 99%